13.1 CCL22 AS A BIOMARKER OF A HIGH-INFLAMMATION PHENOTYPE IN EARLY PSYCHOSIS - Suvisaari, Jaana (Schizophr Bull, 2019)
BACKGROUND: CCL22 is a chemokine that is highly expressed in the thymus and by myeloid cells and produced especially by activated (M2) macrophages and monocyte-derived dendritic cells. It is a potent chemoattractant for antigen-experienced, but not resting, T lymphocytes, and all Th cell subtypes express its receptor. CCL22 signaling through its receptor CCR4 has previously been studied in multiple sclerosis (MS), cancer, asthma and allergies, cardiovascular diseases and autoimmune diseases. Elevated cerebrospinal fluid levels of CCL22 have been reported in MS, and the involvement of CCL22 and CCR4 in the experimental autoimmune encephalomyelitis (EAE) model of MS has been consistently shown (Scheu et al. 2017). We have previously found in a small study of 37 patients with first-episode psychosis and 19 controls that the chemokine CCL22 was markedly elevated in patients with first-episode psychosis (FEP), and elevated CCL22 levels were associated with white matter changes in structural brain imaging and diffusion tensor imaging (Mäntylä et al. 2015). Here, CCL22 and 37 other cyto- and chemokines in a longitudinal study of patients with early psychosis and healthy controls. METHODS: We analyzed a panel of 38 cyto- and chemokines from serum samples in two longitudinal study samples consisting of young adult patients with clinical high-risk state (CHR; N=35), first-episode psychosis (FEP; N=129) and healthy controls (N=130). Patients were assessed at the time of their initial treatment contact and 12 months later, and controls were also assessed twice. RESULTS: We found CCL22 to be highly significantly elevated in patients with CHR and FEP compared to the controls and to remain elevated in a one-year follow-up. After systematic evaluation and adjustment for potential confounding factors like age, gender, BMI, antipsychotic medications, smoking and cannabis use, elevated CCL22 was still highly significantly associated with psychosis. In contrast, only modest or no changes were seen in other cyto- or chemokines. However, above patient median CCL22 levels were associated with marked changes in almost half of the other cyto- and chemokines, and this phenotype persists in the one-year follow-up, suggesting that elevated CCL22 is a biomarker of a high-inflammation phenotype. Moreover, CCL22 levels correlated with symptom severity at both time points. We are currently analyzing whether CCL22 levels are associated with brain structural changes, as measured by MRI and DTI, and these results will be presented in the meeting. CONCLUSIONS: Our results suggest that CCL22 is a trait-like marker of a high-inflammation state in early psychosis. We are performing further studies to determine the mechanism causing CCL22 elevation.